Dataverse Curation Log - Evering, Danica; Pratt, Isaac (McMaster University, 2023)
This McMaster Dataverse Curation Log was adapted from the Dataverse Curation Guide (https://zenodo.org/records/5579820 - framed around the acronym CURATION) which itself was updated and adapted from the Data Curation Network’s CURATE(D) Steps (https://datacurationnetwork.org/outputs/workflows/). Our list aligns with on-the-ground needs and realities of data sharing at McMaster and is intended to be updated as the program expands. Questions are phrased such that “YES” always indicates the dataset is ready for publication.
McMaster Dataverse Curation Log
Keywords: Data Curation; Information Science; Data Repository; Curation Log